2012
DOI: 10.1590/s0102-09352012000600044
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da microbiota bacteriana do queijo de coalho artesanal produzido na região Agreste do estado de Pernambuco

Abstract: RESUMOO objetivo desta pesquisa foi avaliar a qualidade microbiológica e o perfil ácido-láctico do queijo de coalho artesanal. Todas as amostras de queijo apresentaram coliformes totais, termotolerantes e presença de Escherichia coli, porém com os valores dentro dos padrões estabelecidos pela legislação vigente no país. O perfil ácido-láctico estudado mostrou uma microbiota heterogênea, constituída por lactobacilos, lactococos, estreptococos e enterococos, confirmadas as espécies Enterococcus faecalis, Enteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
12
0
3
Order By: Relevance
“…The isolation of Lactococcus sp. in artisanal Coalho cheese in the northeast region has been reported by different authors (Carvalho, 2007;Guedes Neto, Souza, Nunes, Nicoli, & Santos, 2005;Silva et al, 2012). There are no reports in the literature about the isolation and identification of L. garvieae in industrial or artisanal Brazilian cheeses, but the species has been found in cheeses and cow's milk in other countries (Alegría et al, 2009;Alomar, Loubiere, Delbes, Nouaille, & Montel, 2008;Fortina, Ricci, & Borgo, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…The isolation of Lactococcus sp. in artisanal Coalho cheese in the northeast region has been reported by different authors (Carvalho, 2007;Guedes Neto, Souza, Nunes, Nicoli, & Santos, 2005;Silva et al, 2012). There are no reports in the literature about the isolation and identification of L. garvieae in industrial or artisanal Brazilian cheeses, but the species has been found in cheeses and cow's milk in other countries (Alegría et al, 2009;Alomar, Loubiere, Delbes, Nouaille, & Montel, 2008;Fortina, Ricci, & Borgo, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…3 O aroma dos queijos obtidos pela fermentação do leite cru é diretamente associado à raça, ao tipo de nutrição das fêmeas, ao processo de fabricação tradicional e à microbiota autóctone, que é responsável pela fermentação e maturação próprias da região produtora, 4 fornecendo, assim, características diversificadas em locais diferentes. 5 As BAL são empregadas na tecnologia de alimentos por causa de sua contribuição no aroma, textura, valor nutricional e segurança microbiológica em alimentos fermentados, além de serem produtoras de enzimas proteolíticas, exopolissacarídeos 3 e substâncias antimicrobianas, como as bacteriocinas e antibióticos. 6 Devido às suas propriedades metabólicas, as BAL apresentam significativo efeito inibitório sobre o crescimento e a produção de toxinas de muitas outras espécies de bactérias.…”
Section: Introductionunclassified
“…This cheese is mostly produced in small properties, through techniques that are passed down through generations and which present particularities among the various producers (Silva et al, 2012b). Its form of production and characteristics are regulated by the Normative Instruction No.…”
Section: Artisanal Products Of Northeastern Brazilmentioning
confidence: 99%